Malnutrition, Sarcopenia, and Malnutrition Sarcopenia Syndrome in Idiopathic Pulmonary Fibrosis - Eva Cabrera-César; Rocío Fernández-Jiménez; Javier Lopez-Garcia; Alicia Sanmartín-Sánchez; Miguel Benítez Cano-Gamonoso; Isabel Asschert Agüero; Francisco Espíldora-Hernández; Luis Fernandez de Rota Garcia; Isabel Vega-Aguilar; Maria del Mar Amaya-Campos; Francisco J. Tinahones; Jose Manuel Garcia-Almeida; et al. (Advances in Respiratory Medicine)
Introduction: Idiopathic pulmonaryy fibrosis (IPF) is a progressive interstitial lung disease with a poor prognosis. While comorbidities like pulmonary hypertension and lung cancer have been studied extensively, less attention has been paid to the implications of malnutrition and sarcopenia in patients with IPF. This study aimed to assess the prevalence of malnutrition, sarcopenia, and the combined malnutrition-sarcopenia syndrome in patients with IPF using the latest diagnostic criteria from the Global Leadership Initiative on Malnutrition (GLIM) and the European Working Group on Sarcopenia in Older People 2 (EWGSOP2). Methods: A prospective, observational, multicenter study was conducted, focusing on patients with idiopathic pulmonary fibrosis (IPF). All participants provided informed consent, and the study followed ethical guidelines. Malnutrition was diagnosed based on the GLIM criteria, requiring one phenotypic and one etiological criterion, with muscle mass assessed via bioelectrical impedance analysis (BIA). Sarcopenia was screened following the EWGSOP2 recommendations. The statistical analysis was performed using JAMOVI version 2.3.22, with significance set at p < 0.05. Results: The findings revealed that 77.65% of the participants were malnourished, and 20% had sarcopenia. The malnourished patients had significantly lower body weight, height, and muscle mass compared to the non-malnourished patients. Furthermore, the patients with malnutrition exhibited poorer health-related quality of life scores. This study also identified the malnutrition-sarcopenia syndrome in 8.23% of the participants. Conclusions: Malnutrition, based on the GLIM criteria was identified in three out of four patients with IPF, while sarcopenia according to the EWGSOP2 was present in one out of five. This study underscores the necessity for routine screening for malnutrition and sarcopenia in patients with IPF.